English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

I'm trying to understand how to do this one calculus problem but haven't been able to do it with the exponents. Any help appreciated. Thanks.

Find d/dx [sin^4 (x^3)]

2007-02-14 18:39:55 · 6 answers · asked by AppleCard! 2 in Science & Mathematics Mathematics

6 answers

You have to keep using the chain rule. Take the derivative of what's on the outside, which is the exponent: 4 [sin (x³) ] ³

Now multiply that by the derivative of what's immediately inside:
4 [sin (x³)] ³ cos(x³)

And finally multiply it by the derivative of what's inside of the last term you just made:
4 [sin (x³)]³ * cos(x³) * 3x²

Simplify:
(12x²) [sin³(x³)] cos(x³)

2007-02-14 20:19:15 · answer #1 · answered by Anonymous · 1 0

f(x) = sin^4(x^3)

To solve this, you need knowledge of the chain rule.
You're also dealing with three functions here: the 4th power, the sine, and the x^3. d/dx x^4 = 4x^3, d/dx sin(x) = cos(x), and
d/dx x^3 = 3x^2.

I'm going to rewrite the function slightly to make all the functions more obvious.

f(x) = [sin(x^3)]^4

Therefore, by the chain rule (twice),

f'(x) = 4[sin(x^3)]^3 (cos(x^3)) (3x^2)

2007-02-14 18:46:14 · answer #2 · answered by Puggy 7 · 3 0

ok so you're trying to find the derivative of [ sin^4 (x^3) ], which looks like this: [sin(x^3)]^4. so you do the chain rule twice -->
d/dx [sin(x^3)]^4 = 4[sin(x^3)]^3 * cos(x^3) * 3x^2

2007-02-14 18:48:33 · answer #3 · answered by Jerico M 1 · 0 0

y = [ sin ^(4) (x³) ]

Let u = x³

du / dx = 3x²

y = sin^(4) u

dy/du = 4 sin³ u . cos u

dy / dx = (dy / du) . (du /dx)

dy / dx = 4 sin ³ u . cos u . 3x²

dy / dx = 4 sin³ (x³ ) . cos (x³) . 3 x²

dy / dx= 12x² . sin ³ (x ³) . cos (x³)

2007-02-14 20:49:02 · answer #4 · answered by Como 7 · 0 0

15/x(x - 1)(x - 2) = A/x + B/(x - 1) + C/(x - 2) 15 = A(x - 1)(x - 2) + Bx (x - 2) + Cx(x - 1) 15 = A(x^2 - 3x + 2) + B(x^2 - 2x) + C(x^2 - x) 15 = x^2 (A + B + C) + x(-3A - 2B - C) + 2A 2A = 15 ==> A = 15/2 -3A - 2B - C = 0 ==> - 2B - C = 45/2 -----------(1) A + B + C = 0 ==> B + C = - 15/2----------------(2) Add eqns (1) and (2) -B = 15 ==> B = - 15 substitute in (2) C = -15/2 + 15 ==< C = 15/2 A = 15/2, B = -15 and C = 15/2

2016-05-24 01:53:48 · answer #5 · answered by ? 4 · 0 0

d/dx [sin^4 (x^3)] =
[4sin^3(x^3)][cos(x^3)](3x^2) =
(12x^2)[4sin^3(x^3)][cos(x^3)]

2007-02-14 19:06:25 · answer #6 · answered by Helmut 7 · 0 0

fedest.com, questions and answers